Quantitative analysis the completeness of electronic medical summaries for inpatient pediatric at Karya Medika Bantar Gebang Hospital - Khodijah, Siti; Novratilova, Sinta (Science Midwifery, 2025)
Incomplete documentation of pediatric inpatient electronic medical records at Karya Medika Bantar Gebang Hospital affects the quality of medical recordkeeping. A preliminary study revealed completeness rates of 100% for identification, 70% for important reports, 65% for accurate documentation, and 85% for authentication. This study aimed to analyze the factors contributing to these deficiencies. A qualitative descriptive method was applied, involving one medical record officer, two pediatric ward supervisors, and one triangulation informant. The research covered 764 pediatric inpatient electronic medical records from January to June 2025, with a random sample of 88 records determined using the Slovin formula. The results identified five contributing factors: human (incomplete entries by physicians), machine (unstable internet connection), money (no training budget), method (absence of standard operating procedures), and material (lack of tools for completeness analysis). The highest incompleteness occurred in accurate documentation and important reports. In conclusion, the study emphasizes the need to implement a reward and punishment system, provide backup modems, allocate budgets for staff training, establish SOPs in accordance with regulations, and utilize checklists as an evaluation tool.